2019
DOI: 10.1002/adhm.201901106
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pedicle and Microchannels: Simple Methods Toward Effective In Vivo Vascularization of 3D Scaffolds

Abstract: Poor vascularization remains a key limiting factor in translating advances in tissue engineering to clinical applications. Vascular pedicles (large arteries and veins) isolated in plastic chambers are known to sprout an extensive capillary network. This study examined the effect vascular pedicles and scaffold architecture have on vascularization and tissue integration of implanted silk scaffolds. Porous silk scaffolds with or without microchannels are manufactured to support implantation of a central vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Micropatterning for vascularization involves the subtraction of predefined patterns within the engineered matrix to create microchannels that resemble a vascular network. It can be classified into two modalities: micromolding (18,19) and laser degradation (20). Fine-tuned micropatterns on the scaffold provides spatial cues allowing for EC attachment and subsequent 3D-tube formation.…”
Section: Micropatterned Microvasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…Micropatterning for vascularization involves the subtraction of predefined patterns within the engineered matrix to create microchannels that resemble a vascular network. It can be classified into two modalities: micromolding (18,19) and laser degradation (20). Fine-tuned micropatterns on the scaffold provides spatial cues allowing for EC attachment and subsequent 3D-tube formation.…”
Section: Micropatterned Microvasculaturementioning
confidence: 99%
“…For example, Teflon coated wires with a diameter of 500 µm incorporated into a silk-based scaffold act as a mold for fabricating microchannels within a thick silk scaffold (7 mm). These channels allowed vascularization within 2 weeks postimplantation in mice (19). However, a simple tubular mold cannot capture the complexity of natural microvasculature within the tissue.…”
Section: Micropatterned Microvasculaturementioning
confidence: 99%
“…15,16 A few reports of silk based lyogels have been published and it has been demonstrated that the crosslinked nature of the starting protein network results in unique physicochemical properties compared to lyophilized sponges made by lyophilizing uncrosslinked silk solution. 14,[16][17][18][19] While lyophilized silk sponges have been widely explored and evaluated for applications such as soft tissue, [20][21][22] intervertebral disc, 23 and cardiovascular tissue [24][25][26] augmentation and regeneration, platelet production, 27 and drug delivery, 28,29 silk lyogels are less well characterized. In particular, the properties of silk lyogels made from di-tyrosine crosslinked silk networks have not been explored to date.…”
Section: Introductionmentioning
confidence: 99%
“… 28 Neovascularization is a delayed process (almost 15 days) and depends on graft thickness. Whereas inosculation, the formation of functional connections with host capillaries, 29 is a thickness independent and fast process (<4 days) [ Fig. 3(a) ].…”
Section: Tissue Engineering Strategies For Therapeutic Angiogenesismentioning
confidence: 99%